Heat treatment 80Х3СВФ became with the use of cooling in the friable graphite - Заблоцкий, Владимир Кириллович; Шимко, Владимир Игоревич; Шимко, Алексей Игоревич (Eastern-European Journal of Enterprise Technologies, 2012)
Processes, flowing at the continuous cooling 80Х3СВФ became from the temperature of austenitization in a friable graphite, are studied, on air and with a stove, it is set that with diminishing of cooling speed duration of pearlite transformation is increased.